Treatment of Elderly Parkinson's Suffers by Carrying Out Stretching Exercise Therapy at Aiwakai Medical Corporation Ikedaen Okinawa Japan - Aushofi, Kamelia; Jati, Riani Pradara (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Parkinson's disease is the second most common neurodegenerative disorder suffered by many people after Alzheimer's disease. Parkinson's disease sufferers experience several symptoms, such as intellectual and behavioral disorders, dementia, memory loss, muscle weakness, catalepsy (slow and stiff movements) and tremors. Parkinson's disease is a disease that includes brain nerve disorders that trigger various problems such as the body's motor skills. Objective to provide information about the treatment of stretching exercise therapy to Parkinson's patients in increasing muscle strength, muscle balance, and fluency in communicating with everyone. The case study in this research uses a nursing approach method, such as assessment, nursing diagnosis, intervention, implementation, and evaluation. The intervention given to patients in this study was walking exercises with parallel bar physiotherapy. After being carried out for 3 days, it was able to increase muscle strength in Parkinson's patients, for example the patient showed that he could walk with the help of a nurse. Providing stretching exercise therapy intervention can improve balance in the leg muscles.